1984
DOI: 10.1136/jnnp.47.11.1219
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve involvement in sarcoidosis: an electrodiagnostic study.

Abstract: SUMMARY The frequency of peripheral nerve involvement in sarcoidosis is uncertain. To determine how often peripheral nerves are affected in the absence of symptoms, electromyography was performed on 29 sarcoid patients and 29 age-matched controls. Nineteen sarcoid patients, compared to two controls, had abnormally low sensory amplitudes in one or more nerves, and the mean sensory amplitudes for median, ulnar, and sural nerves were lower in the patient than in the controls. Subclinical mononeuropathy multiplex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Estimates of the incidence of peripheral nerve involvement in sarcoidosis vary widely. There is pathologic or electrophysiological evidence of peripheral neuropathy even in asymptomatic cases, although these are not typically investigated in practice 4–7, 10. Axonal degeneration is far more prominent than demyelination based on electrodiagnostic studies, which is consistent with the infiltrative granulomatous process seen pathologically 4, 7.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Estimates of the incidence of peripheral nerve involvement in sarcoidosis vary widely. There is pathologic or electrophysiological evidence of peripheral neuropathy even in asymptomatic cases, although these are not typically investigated in practice 4–7, 10. Axonal degeneration is far more prominent than demyelination based on electrodiagnostic studies, which is consistent with the infiltrative granulomatous process seen pathologically 4, 7.…”
Section: Discussionmentioning
confidence: 79%
“…Nervous system involvement has been reported in up to 4% of patients with sarcoidosis, of whom 70% present initially with neurological symptoms 1–3. Among sarcoidosis patients without neurological symptoms, at least one third will have subclinical evidence of nervous system involvement on pathologic review at autopsy 4–6. Cranial neuropathies are the most common neurological manifestations of sarcoidosis.…”
mentioning
confidence: 99%
“…Postmortem studies, such as the one published by Iwai et al, 16 suggest that antemortem diagnosis of central nervous system involvement is only made in one-half of the patients with sarcoidosis. Furthermore, in the electrophysiological studies reported by Challenor et al, 17 with 2 of 29 age-matched controls. Sensory evoked potential studies showed abnormally low sensory amplitudes in at least 1 peripheral nerve examined, although EMG and nerve conduction studies were normal.…”
Section: Discussionmentioning
confidence: 94%
“…The frequency of peripheral nerve involvement in sarcoidosis is uncertain but there seem to be many asymptomatic cases 10. Zajicek1 proposed diagnostic criteria with levels of certainty and these criteria are commonly used.…”
Section: Introductionmentioning
confidence: 99%